Tribes and cultures : frameworks for shared language and intent to cost effectively improve learning outcomes. - Dreher, Heinz; Quinton, Stephen; Dreher, Naomi; LeClus, Megan; Dreher, Carl; Herrmann, Allan (Australian Learning and Teaching Council, 2011)
In this project we proposed formal clarification of the shared language and the meaning of the pedagogical concepts as used by knowledge domain experts, educational designers, educational technologists, programmers and most importantly for evaluation purposes, the students and their teachers who are the end users in this context. Our motivation was the observable fact, and experience, that much of the educational software available today exhibits the hallmarks of its technical creators and shrouds its features and usability in jargon and unfamiliar methods with which the end-user experiences difficulty, incongruity with their own mental models, and unwarranted complexity, potentially leading to ineffective use, and cost-inefficiencies. -- ALTC Website